Experimental investigation of free head model piles under lateral load in homogenous and layered sand. Issue 4 (September 2015) - Bisaws, S. K.; Mukherjee, S.; Chakrabarti, S.; De, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Model pile tests were carried out and subsequently the experimental study was supplemented by numerical study to determine coefficient of horizontal modulus of sub-grade reaction (ηh). Both short and long free headed piles were tested in homogeneous and layered soil media. Relative density of sand, slenderness ratio (SR), and embedment ratio of pile (thickness of top weaker layer) were varied. The numerical study was done by three-dimensional finite element method with the help of PLAXIS 3D Foundation version 2.1 software. Then, finite difference method was applied on the deflection profile along pile depth obtained from output of finite element analysis to determine ηh, the coefficient of horizontal modulus of sub-grade reaction. In finite element analysis, the test conditions were simulated and variables of the same soil–pile parameters were considered as in case of the experimental study. The numerical results were found to agree considerably well with the experimental ones for both long and short piles in homogeneous and layered sand media. Subsequently, variation of ηh was studied with the soil–pile parameters as mentioned. The variation of normalised form of ηh, defined as flexibility ratio with different soil–pile parameters, was also studied. At the outset, some behavioural changes were noted for long and short piles in both homogeneous and layered sand. In case of layered sand medium, ηh increased as the overlying weaker sand layer thickness decreased. However, in case of short piles and long piles, this variation was continuously linear. For short piles, ηh increased with increase in sand compactness and SR of pile, whereas in case of long piles, it increased with sand compactness and decreased with the SR of pile beyond SR of 40. This paper focuses on change on variation of different soil–pile parameters on ultimate lateral load as well as coefficient of horizontal modulus of sub-grade reaction (ηh), the principle stiffness parameter, which determines the ultimate lateral load of a single pile.